Rare case: enucleation of multiple fibroids after intraoperative vaginal sonographic detection of the solitary pelvic kidney by patient with Mayer-Rokitansky-Kuster-Hauser syndrome - Piriyev, Elvin; Romer, Thomas (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Mayer-Rokitansky-Kuster-Hauser syndrome (MRKH) is a congenital anomaly of the genital tract that occurs in about 1 in 4000 women. MRKH syndrome can be associated with renal, skeletal, heart and hearing abnormalities. The frequency of renal/urinary tract abnormalities is 33%. Only a few cases of fibroid development in MRKH syndrome have been described in the literature. The diagnosis and surgery of a fibroid in MRKH syndrome may be complicated in associated kidney abnormality by an atypical kidney position, as in this case: pelvic kidney on one side and renal agenesia on the contralateral side. Authors present the case of a 47-year-old female patient with a known MRKH syndrome and a pelvic kidney on the right side who had presented with an unclear tumour in the right lower abdomen. A completed CT scan revealed the tumour directly next to the pelvic kidney. A malignancy could not be excluded with certainty, so that a laparoscopy in laparotomy readiness was indicated and performed. During surgery, two rudimentary uterine horns were found; on the right side retroperitoneally, below the uterine horn, the tumour was located and directly below it there was a soft tissue alteration, probably the kidney. For safety, a vaginal sonography was performed in between, to clearly identify the only kidney and to avoid damaging it. The tumour could be extirpated laparoscopically without kidney injury. The two uterine horns were removed simultaneously. Histologically the fibroid could be confirmed. In addition, three other fibroids (one on the left side and two on the right side) were detected. Due to the high probability of a simultaneous kidney abnormality in the MRKH syndrome, authors suggest an accurate kidney diagnosis preoperatively. If necessary, in the case of a pelvic kidney and/or renal agenesia, as in this case, an additional intraoperative kidney check should be performed.